For the glory of god: recovering a biblical theology of worship - Block, Daniel Isaac (Baker Academic, 2016)
"Respected Old Testament scholar Daniel Block examines worship in the Bible, offering a comprehensive biblical foundation and illuminating Old Testament worship practices and principles. He develops a theology of worship that is consistent with the teachings of Scripture and is applicable for the church today. He also introduces readers to a wide range of issues related to worship. The book, illustrated with diagrams, charts, and pictures, will benefit professors and students in worship and Bible courses, pastors, and church leaders." -- Amazon